Pandangan Terhadap Kematian Dalam Perspektif Al-Quran Dan Ilmu Kedokteran Modern - Wildan Hersa Syakir; Andrea Adisa; Mohamad Faqih Cakradipura; Astrella Syakira Honey; Lutfiah Syafiqoh (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Al- Quran a part from its position as the main source of Islamic teachings, the Koran is also a significant one. Therefore, since the time of the Prophet Muhammad SAW, and his companions until now, the ulama have produced various works of interpretation with a variety of methods and styles as their reflection on the Al-Quran. However, these interpretations are not an easy thing, because a person's understanding cannot be separated from several factors such as scientific background, experiences, socio-political conditions and so on. The problem regarding the view of death is that recently there has been no clear definition of death, as a result of increasingly sophisticated technology and also the existence of several deaths before entering the era of technological sophistication. Death in the world of modern medicine has the definition of the end of certain biological functions, the cessation of vital organs. such as breathing, heart rate, or blood pressure. However, advances in medical technology have given rise to controversy regarding what criteria should be used to determine whether a person is dead, because currently, in the world of modern medicine, the reference for determining death is the death of the brain stem (brain death).